Transitional justice in peacebuilding : actor-contingent and malleable justice - Ostowar, Djeyhoun, 1987- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book develops a novel, actor-centred framework for studying transitional justice in peacebuilding contexts. In recent decades, transitional justice mechanisms and processes have been introduced to a variety of settings and are widely regarded as essential elements in the 'peacebuilding toolbox'. While some critics suggest that transitional justice is imposed by neo-imperial actors with little regard for the needs and cultures of local populations, evidence suggests that dismissing these policies as neo-imperial or neo-liberal impositions would result in grossly overlooking their dynamics, which involve a whole range of relevant actors operating at multiple levels. This book interrogates this theme through empirical analysis of three sites of peacebuilding that have seen extensive international involvement: Afghanistan, Kosovo and East Timor. It proposes a framework that disaggregates three broad sets of actors operating at different levels in peacebuilding processes: external actors (international and regional levels), transitional justice promoters (local, national, international and transnational levels), and transitional regimes (national and local levels). The book argues that transitional justice in peacebuilding must be conceived of as actor-contingent and malleable due to the significance of agency and (inter)actions of key categories of actors throughout peacebuilding transition. This book will be of interest to students and practitioners of transitional justice, peacebuilding, law, and International Relations"--
OCLC-licensed vendor bibliographic record.
Keywords: Peace-building.; Transitional justice; POLITICAL SCIENCE / Peace; POLITICAL SCIENCE / Political Freedom & Security / Human Rights; POLITICAL SCIENCE / International Relations / General